Recapitulation of primary nailing in open diaphyseal fractures of tibia - Theeppainthan, Pradeepkumar; Sundaram, Thayumana; Anbalagan, Prabhakaran; Pandiyan, Selvakumar; Rajasekaran, Chitarth; Pandiyan, Hemnath (International Journal of Research in Orthopaedics, 2019)
Tibia fractures are the commonest long bone fracture, most commonly resulting from high velocity injury. We investigated whether primary nailing in open tibia fractures were producing satisfactory outcomes and we compared the outcomes in terms of fracture union and rates of infection. We identified 202 citations related to our searches from our key words, out of which 89 were original articles, which were eligible and others were case reports and review articles. We found 4 from these references which had the parallel inclusion criteria and were reviewed. All 4 studies had almost similar time period for the fracture union. Infection rates in this study were directly related to the severity of the grade of injury, which were commonly experienced in grade III injuries. In conclusion, our analysis had no significant difference in postoperative healing duration, implant failure rates, postoperative infection and secondary operation rates in primary nailing for open tibia fractures.